Fortunella venosa (Champ. ex Benth.) C. C. Huang and F. hindsii (Champ. ex Benth.) Swingle as Independent Species: Evidence From Morphology and Molecular Systematics and Taxonomic Revision of Fortunella (Rutaceae) - Wang, Ting; Chen, Ling-Ling; Shu, Hui-Juan; You, Fang; Liang, Xiao-Li; Li, Jun; Ren, Jing; Wanga, Vincent Okelo; Mutie, Fredrick Munyao; Cai, Xiu-Zhen; Liu, Ke-Ming; Hu, Guang-Wan (Frontiers in Plant Science, 2022)
Recently, the systematic status of Fortunella Swingle and its taxonomy has attracted much attention. Flora of China incorporates Fortunella into Citrus Linn and treats all species of the traditional Fortunella as one species, namely Citrus japonica (Thunb.) Swingle. Furthermore, Fortunella venosa (Champ. ex Benth.) C.C. Huang and Fortunella hindsii (Champ.) Swingle are currently considered as synonyms of C. japonica. In this paper, morphological, Palynological, and phylogenetic analyses were used to systematically explore the taxonomic status of traditional Fortunella. The key morphological features that differed among the Fortunella species were the leaf and the petiole hence could be key in its Taxonomic classification of the species. Additionally, Pollen morphology analysis based on the pollen size, germination grooves, polar and equatorial axes also supported the separation of the species. The results of the phylogenetic analysis showed that each of the three species clustered separately branch, hence strongly supporting the conclusion of independent species. In addition, the phylogenetic analysis showed that the two genera clustered closely together hence our results support the incorporation of Fortunella into Citrus. Based on the above, this article has revised the classification of the traditional Fortunella and determined that this genus has three species, namely; F. venosa, F. hindsii, and F. japonica. F. venosa and F. hindsii are placed in the Citrus as separate species, and their species names still use the previous specific epithet. The revised scientific names of the new combinations of F. venosa and F. hindsii are as follows: Citrus venosa (Champ. ex Benth.) K.M. Liu & X.Z. Cai, comb. nov. and Citrus hindsii (Champ. ex Benth.) K.M. Liu & G.W. Hu, comb. nov. F. venosa is the original species of Fortunella, F. venosa and F. hindsii are both listed as the second-class key protected wild plants in China. Therefore, the establishment of the taxonomic status of F. venosa and F. hindsii not only deepens our understanding, importance, and the complexity of the systematic classification of Fortunella, but also is significant for global biodiversity conservation, genetic resources for breeding purposes, and population genetics.